Diabetes and obesity. The role of agonists glucagon-like peptide-1 of in the treatment of type 2 diabetes - Nina A. Petunina (Endocrinology Research Centre, 2018)
Significant number of patients with type 2 diabetes mellitus are obese. It is known that even glucose intolerance, as well as diabetes, can lead to vascular complications. At the same time, weight loss can reduce the risk of type 2 diabetes in obese and pre-diabetic patients. According to available data, a significant decrease in the incretin effect is observed in patients with type 2 diabetes and obese individuals. Thus, a decrease in the incretin effect leads to a violation of the insulin response to the intake of carbohydrates, and, consequently, an increase in the level of glucose in the blood. It was also found that the decrease in the incretin effect in patients with type 2 diabetes can be associated with a lower secretion of glucagon-like peptide-1. The interest is represented by groups of antidiabetic drugs capable of regulating glycemia by affecting the secretion of insulin and glucagon, depending on its level. Such drugs include glucagon-like peptide-1 receptor agonists. The article shows the advantage of prolonged action in patients with type 2 diabetes and obesity of the glucagon-like peptide 1 receptor agonists (albiglutide, dulaglutide, exenatide with slow release) dosing 1 time a week.